Correlation Between TCF7+ T Cells and Prognosis of Patients With Oral Squamous Cell Carcinoma - Rong, Haixu; Cai, Tingting; Peng, Yu; Wang, Xiaojuan; Lan, Tianjun; Ou, Zhanpeng; Qiu, Ling; Li, Qunxing; Zhang, Lizao; Wu, Fan; Lin, Hsinyu; Ren, Siqi; et al. (Frontiers in Oncology, 2022)
Objective To investigate whether TCF7+ T cells constitute an important factor to improve the existing postoperative prediction model for patients with oral squamous cell carcinoma. Method TCF7+ T cells were detected in the tissues of 167 OSCC patients by multiplex immunofluorescence. The percentage of TCF7+ T cells was transformed into a dichotomous variable, combined with the clinicopathological data for the OSCC patients, and then subjected to univariate and multivariate analyses. The derived independent predictors were then incorporated into risk models to analyze their relationship with the prognosis of patients. Results The high TCF7+ group had a better prognosis than the low TCF7+ group (OS: p<0.001; RFS: p<0.001). Univariate and multivariate analyses showed that TCF7+ T cells serve as an independent predictor of OSCC (univariate/multivariate analysis: p<0.001). In Cox risk progression models, inclusion of the TCF7+ T cell percentage improved the predictive accuracy of Grade and TNM stage (Grade-OS/RFS: p<0.001; TNM-OS/RFS: p<0.001; TNM+Grade-OS: p<0.001, TNM+Grade-RFS: p=0.004). Inclusion of the TCF7+ T cell percentage improved the clinical utility. Conclusions TCF7+ T cells can act as an independent predictor for postoperative OSCC patients. The inclusion of TCF7+ T cells improved the predictive accuracy and clinical utility of the nomograms to different degrees.